Navigating the winds of change : presentation of wind power development by regional newspapers in Northern Sweden and Finland - Bjärstig, Therese; Lempinen, Hanna (Springer Nature, 2025)
Background: Dramatic reductions in anthropogenic CO2 emissions are needed to mitigate the impacts of rapidly accelerating climate change. In Sweden and Finland efforts to realize the political ambitions to meet international climate objectives, and promote the growth of ‘green’ industries, have focused on rapid expansion of wind farms, but in both countries wind power developments have been controversial. These controversies are especially prominent in the northern regions of the countries which have become hotspots of wind power development. In this article, we focus on these regional wind power debates with the aim to extend scholarly understanding of the spatial justice dimensions of how ‘just’ and ‘green’ transitions unfold. We do this by examining representations of the ways in which the effects of regional wind power development, their management and the ‘right’ places for wind power are debated in 372 articles in Swedish and Finnish regional news media published during 2020–2023. Results: In regional media representations, wind power is discussed in terms of a wide range of experienced and potential impacts. Negative impacts including harm to the environment, biodiversity and human health are discussed. Yet, the positive effects are emphasized, including contributions to national policy goals and the regional socioeconomic benefits of the emergence of a green, low-carbon economy in both the Swedish and Finnish articles. However, envisioned means for managing wind power development in a fair manner differ: compensations and the right to municipal veto are strongly highlighted in the Swedish articles, while Finnish articles focus on the integrity of democratic processes and planning. As the green transition continues to unfold, northern regions are increasingly being represented as the ‘right’ places for wind power, both from outside and within those regions. Conclusions: Our findings highlight the perceived importance of local and regional socioeconomic benefits and local self-determination for positive perceptions of large-scale wind power developments in our focal administrative and legal contexts. Local and regional histories and encounters with earlier resource development continue to shape reactions to and interpretations of resource development projects in contemporary Euro-Arctic North.